Pedagogical Factor in the Life of Yakov Hal’chevs’kyi - Krasnosilets’kyi, Denys (Pedagogical Discourse, 2012)
Life activity of the etacher, officer, leader of insurgent and underground movement Yakov Hal’chevs’kyi has been analyzed in the article.